Influence of Leadership Style and Technology Skills on Employee Performance: Research at the Baleharjo Village Office, Kapanewon Wonosari, Gunungkidul Regency - Pandu Sinawung Jati (Politeknik Negeri Semarang, 2026)
This study aims to analyze the influence of leadership style and technological skills on employee performance at the Baleharjo Village Office, Kapanewon Wonosari, Gunungkidul Regency. This study uses a quantitative approach with saturated sampling techniques involving 30 respondents as a research sample. The research instrument is in the form of a questionnaire that has been tested for validity and reliability. The data analysis technique used multiple linear regression with the help of the SPSS 22 program. The results of the study show that leadership style has a positive and significant effect on employee performance with a significance value of 0.008 and a regression coefficient of 0.225. Technology skills also have a positive and significant effect on employee performance with a significance value of 0.000 and a regression coefficient of 0.397. Simultaneously, the two independent variables had a significant effect on employee performance with a significance value of 0.000 and a determination coefficient (R²) of 0.797 or 79.7%. These findings indicate that a combination of effective leadership and adequate technology mastery is a key factor in improving employee performance in the era of digitization of public services. This study recommends the need for the development of leadership training programs and the improvement of technological competencies in a sustainable manner to optimize the performance of village government organizations.